Surface wettability effect of plain and plasma-sprayed copper-coated surfaces on CHF enhancement during saturated pool boiling of FC-72. (May 2022) - Mohanty, Rajiva Lochan; Moharana, Subhakanta; Das, Mihir Kumar
In the current scenario, CHF study is essential for the safe operation of electronics equipment comprising a two-phase heat transfer process. Therefore, the present experimental investigation involves saturated pool boiling and CHF study of FC 72 over a plain stainless steel surface (SS) and microporous copper-coated SS surfaces under atmospheric conditions. Accordingly, three different plasma-sprayed copper-coated surfaces with coating thicknesses of 65 μm, 105 μm, and 145 μm prepared using micro copper particles of size 25–45 μm. The analysis of the results shows that with an increase in heat flux values, the boiling heat transfer coefficient increases over plain as well as coated surfaces. The plasma-spayed copper-coated surfaces with a coating thickness of 65 μm and 105 μm exhibit a higher boiling heat transfer coefficient as than the plain surface. On the other hand, a 145 μm thick coated surface resulted in a comparable boiling heat transfer coefficient with the plain SS surface. Among the three porous-coated surfaces, the boiling heat transfer coefficient decreases continuously from 65 μm to 145 μm of the coated surface. On the contrary, to the observed nucleate boiling behavior, all the porous-coated surfaces show a higher value of CHF than the plain surface, and the CHF value is found to increase continuously from 65 μm to 145 μm of the coated surfaces. The enhancement of CHF values was found to be 66.29%, 69.17%, and 77.75% for a coating thickness of 65 μm, 105 μm, and 145 μm, respectively, compared with the plain surface. The porous coating thickness of 65 μm shows a greater value of heat transfer coefficient than 105 μm and 145 μm whereas 145 μm exhibits a higher value of CHF as than 65 μm and 105 μm.